Potensi Radiasi Gelombang Elektromagnetik Extremely Low Frequency (ELF) Guna Meningkatkan Ketahanan Usia Simpan Buah-Buahan - Umi Uswatun; Sudarti Sudarti (PROGRAM STUDI MESIN DAN PERALATAN PERTANIAN, 2022)
Fruits are included in foodstuffs that provide many benefits for the body, but fruits have a relatively short shelf life. ELF (Extremely Low Frequency) magnetic field radiation is radiation with a low frequency of around 0–300 Hz with non-ionizing properties or no effect on the atoms of a material it is subjected to and non-thermal or does not cause an increase in temperature when interacting with a material. In addition, Extremely Low Frequency (ELF) magnetic field radiation can be used for food tenacity. This study aims to determine how much influence ELF radiation has on the shelf life of various types of fruits. The method used in this study is the journal review method, the number of journals reviewed is 11 journals. The journal in question can be in the form of scientific articles and other journals that support and are relevant to the research title. The results of this study indicate that exposure to the ELF magnetic field can maintain the content of vitamin C, maintain the physical condition of the fruits, and increase the shelf life of fruits by maintaining pH by slowing down or increasing the pH, this is done by killing acid-forming microorganisms, In addition, exposure to the ELF magnetic field can reduce the respiration rate and the rate of ethylene production in fruits, this has an impact on extending the shelf life of fruits. The intensity and duration of exposure to the ELF magnetic field must be adjusted to the type and character of the fruit itself. Thus, it can be concluded that exposure to Extremely Low Frequency (ELF) magnetic fields are able to maintain vitamin C content, maintain the physical condition of fruits, and increase the shelf life of fruits.